Short straw - Woods, Stuart; Kramer, Michael (New York : Penguin Audio, 2006)
Having married the seductive Barbara Kennedy against his better judgment, Santa Fe lawyer Ed Eagle awakens the morning after his fortieth birthday to discover that his wife has vanished and that all of his money has been wired to Mexico.
Compact disc.
"An Ed Eagle novel"--Container.
Read by Michael Kramer.
Keywords: Attorney and client; Santa Fe (N.M.); New Mexico -- Santa Fe; Audiobooks; Mystery fiction; Fiction